Next level basic : the definitive basic bitch handbook - Schroeder, Stassi (Gallery Books, 2019)
Millions of Vanderpump Rules viewers and podcast listeners know Stassi Schroeder as a major defender of Basic Bitch rights. There<U+2019>s nothing more boring than people who take themselves too seriously or think that you have to be pretentious to be cool. Stassi champions the things that many of us are afraid to love publicly for fear of being labeled basic: lattes, pugs, bubbly cocktails, millennial pink, #OOTD (outfit of the day, obvs), astrology, hot dogs, the perfect pair of Louboutins, romantic comedies...the list goes on and on. This book is for people tired of pretending they would rather see a Daniel Day-Lewis movie about sewing or read War and Peace than watch a Saw marathon or read...well, this book! In Next Level Basic, the reality star, podcast queen, and ranch dressing expert gives you hilarious and pointed lessons on how to have fun and celebrate yourself, with exclusive stories from her own life and on the set of Vanderpump Rules. From her very public breakups to her most intimate details about her plastic surgery, Stassi shares her own personal experiences with her trademark honesty<U+2014>all with the hope you can learn something from them.